Implementing sustainable innovation in state universities: Process and tools. (10th March 2023) - Rotondo, Federico; Giovanelli, Lucia; Ezza, Alberto
Abstract: Universities have the vision, the knowledge and the power to lead the change towards a more sustainable world. However, there is a lack of studies investigating how universities can systematically reorient themselves to help society become more sustainable. In general, a research gap exists in the implementation of the business model innovation process, in the tools that should be used to pass from the design stage to implementation and in the identification of the main challenges that may hinder this process. This paper adopts the concept of a sustainable business model for interpreting the core logic through which universities create value for themselves, society and the environment. In the first stage of research, a theoretical framework was proposed for diagnosis of the integration of sustainability in the business models of universities. This framework was applied in the context of Italian state universities to identify business models with different degrees of strategic orientation towards sustainability. Now the research aim is to examine the processes and tools used and challenges faced by Italian state universities when implementing sustainable innovation. A multiple-case study is carried out on four Italian state universities showing a high level of integration of sustainability in all elements of the business model. The combination of both quantitative and qualitative data, and the patterns observed across cases, led to the presentation of five theoretical propositions, which were summarized in a preliminary model of the processes, tools and challenges involved when implementing sustainable innovation in higher education. The main theoretical contributions of this study are the advancement of knowledge regarding the dynamics (process) and the elements (tools) for the implementation of sustainability strategies in state universities, and the provision of a new causal map of the relationships among the variables that affect sustainable innovation in higher education. Highlights: Financial support for sustainable innovation is low for Italian state universities. Sustainable innovation for Italian state universities is an incremental process. Sustainable innovation is based on core competences and increased relationships. Drivers and aims determine strategies and degrees of business model innovation. A set of tools are needed to implement sustainable innovation and overcome barriers.